Design, Implementation, and Evaluation of a Fingerprint-Based Ignition Key for Motorcycles - Heru Supriyono; Anugrah Adi Wijayanto; Rozita Jailani; Mohammad Osman Tokhi (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2020)
Cases of motorcycle theft by breaking mechanical key are still a serious problem in some countries. Therefore, this article discusses the process of development, implementation, and evaluation of a fingerprint-based ignition key for motorcycles. To prevent theft, a motorcycle can only be turned on by a registered fingerprint, and an alarm will ring if the sensor receives an unregistered fingerprint. This prototype used the main component of the SEN0188 fingerprint sensor, Arduino Uno microcontroller, LM317 voltage regulator, and the buzzer alarm module. The test results in shaded place showed that the proposed key successfully ignited the engine by 80% with a dry and clean thumb. However, if the thumb is oily or dirty, the success scanning rate is only 36% of 25 attempts. The proposed key also successfully activates a warning alarm if a fingerprint scan attempt fails three times in a row. Test results on potholes, bumpy, dusty, and puddles roads indicate that no hardware has been disturbed or damaged. Therefore, this prototype has the potential to be further developed and implemented on a large scale in an effort to reduce motorcycle theft rates.